3D printed anatomical medical models (Transactions on Additive Manufacturing Meets Medicine, 2023)
This tutorial serves as an introduction to 3D Printing anatomical models in the medical field. We will review application areas, discuss model types and categories, introduce available resources and show examples. We will introduce the approach to developing your own models from DICOM imaging data,segmentation software and resources and virtual model processing as well as 3D model preparation and printing. We will discuss and show representative models from the basic printer technologies and materials currently available.
Keywords: anatomical models